Safety, immunogenicity and dose ranging of a new Vi-CRM₁₉₇ conjugate vaccine against typhoid fever: randomized clinical testing in healthy adults. - Pierre van Damme; Froukje Kafeja; Alessandra Anemona; Venere Basile; Anne Katrin Hilbert; Ilse De Coster; Simona Rondini; Francesca Micoli; Rana M Qasim Khan; Elisa Marchetti; Vito Di Cioccio; Allan Saul; et al. (PLoS ONE, 2011)
Typhoid fever causes more than 21 million cases of disease and 200,000 deaths yearly worldwide, with more than 90% of the disease burden being reported from Asia. Epidemiological data show high disease incidence in young children and suggest that immunization programs should target children below two years of age: this is not possible with available vaccines. The Novartis Vaccines Institute for Global Health developed a conjugate vaccine (Vi-CRM₁₉₇) for infant vaccination concomitantly with EPI vaccines, either starting at 6 weeks with DTP or at 9 months with measles vaccine. We report the results from a Phase 1 and a Phase 2 dose ranging trial with Vi-CRM₁₉₇ in European adults.Following randomized blinded comparison of single vaccination with either Vi-CRM₁₉₇ or licensed polysaccharide vaccines (both containing 25·0 µg of Vi antigen), a randomised observer blinded dose ranging trial was performed in the same center to compare three concentrations of Vi-CRM₁₉₇ (1·25 µg, 5·0 µg and 12·5 µg of Vi antigen) with the polysaccharide vaccine.All vaccines were well tolerated. Compared to the polysaccharide vaccine, Vi-CRM₁₉₇ induced a higher incidence of mild to moderate short lasting local pain. All Vi-CRM₁₉₇ formulations induced higher Vi antibody levels compared to licensed control, with clear dose response relationship.Vi-CRM₁₉₇ did not elicit safety concerns, was highly immunogenic and is therefore suitable for further clinical testing in endemic populations of South Asia.ClinicalTrials.gov NCT01123941 NCT01193907.